2018
DOI: 10.1136/jramc-2018-001031
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic haemorrhage in military major trauma patients: a retrospective database analysis of haemostatic agents used on the battlefield

Abstract: ObjectivesCatastrophic haemorrhage is a leading cause of morbidity and mortality in trauma, in both military and civilian settings. There are numerous studies looking at the effectiveness of different haemostatic agents in the laboratory but few in a clinical setting. This study analyses the use of haemostatic dressings used in patients injured on the battlefield and their association with survival.MethodA retrospective database review was undertaken using the UK Joint Theatre Trauma Registry from 2003 to 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
12
0
3
Order By: Relevance
“…Two studies reported a higher incidence of wound infections with tourniquet use 15 16. Four studies investigating the use of hemostatic dressings (HemCon (HemCon Medical Technologies, Portland, Oregon), QuikClot Combat Gauze (Z-Medica, Wallingford, Connecticut) or Celox (SAM Medical, Tualatin, Oregon)) demonstrated effective hemorrhage cessation and overall improved survival compared with non-hemostatic dressings 8 14 20 22…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported a higher incidence of wound infections with tourniquet use 15 16. Four studies investigating the use of hemostatic dressings (HemCon (HemCon Medical Technologies, Portland, Oregon), QuikClot Combat Gauze (Z-Medica, Wallingford, Connecticut) or Celox (SAM Medical, Tualatin, Oregon)) demonstrated effective hemorrhage cessation and overall improved survival compared with non-hemostatic dressings 8 14 20 22…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs46 61 63 had low risk of bias (tables 2–4, and online supplemental table 3). Forty-three (78%) of non-randomized cohort studies were classified as having poor evidence quality8 10–15 18–33 35 38 40–43 45 49 51 52 54 55 57–59 69 70 and 12 (22%)16 17 36 37 44 47 50 53 56 60 65 66 had good evidence quality as per the NOS. In addition, the diagnostic studies68–70 included in this review had a high overall risk of bias as per QUADAS-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhage is a leading cause for death. [1,2] Uncontrolled bleeding is reported to contribute to 34% of the deaths in accidents and 91% of the battle field death. [2,3] The conventional method for hemorrhage control is to mechanically press a cotton gauze/dressing on a bleeding wound; [4,5] the cotton gauze absorbs water and increases the concentration of clotting factors such as platelets around the wound, expediting the tissue-adhesive interface by a triggering solution.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, the severity and number of wounds exacerbate the challenge of controlling bleeding quickly [8]. In a metaanalysis within a combat setting, where minimising treatment time is critical, Celox Gauze outperformed the other haemostatic agents tested, and was the only one to demonstrate a statistically significant improvement in survival, including in the more severely injured [9].…”
mentioning
confidence: 99%